2010
DOI: 10.1590/s0100-06832010000500005
|View full text |Cite
|
Sign up to set email alerts
|

Water-dispersible clay in soils treated with sewage sludge

Abstract: SUMMARYA by-product of Wastewater Treatment Stations is sewage sludge. By treatment and processing, the sludge is made suitable for rational and environmentally safe use in agriculture. The aim of this study was to assess the influence of different doses of limed sewage sludge (50 %) on clay dispersion in soil samples with different textures (clayey and medium). The study was conducted with soil samples collected from native forest, on a Red Latosol (Brazilian classification: Latossolo Vermelho distroférrico) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 20 publications
2
13
0
7
Order By: Relevance
“…Convém destacar que o desenvolvimento da estrutura do solo inicia-se com o fenômeno da floculação, porém, somente após a ação prolongada da matéria orgânica e de compostos do solo, é que adquire a estabilidade necessária (Bayer & Mielniczuk, 2008). Entretanto, em Latossolo Vermelho e Latossolo Vermelho-Amarelo, os quais possuem naturalmente alto grau de floculação, Tavares Filho et al (2010) não constataram diferenças significativas, quanto aos teores de argila dispersa em água, entre solos adubados com lodo de esgoto, em doses de até 48 t ha -1 , e solos não adubados com o resíduo orgânico.…”
Section: Variávelunclassified
“…Convém destacar que o desenvolvimento da estrutura do solo inicia-se com o fenômeno da floculação, porém, somente após a ação prolongada da matéria orgânica e de compostos do solo, é que adquire a estabilidade necessária (Bayer & Mielniczuk, 2008). Entretanto, em Latossolo Vermelho e Latossolo Vermelho-Amarelo, os quais possuem naturalmente alto grau de floculação, Tavares Filho et al (2010) não constataram diferenças significativas, quanto aos teores de argila dispersa em água, entre solos adubados com lodo de esgoto, em doses de até 48 t ha -1 , e solos não adubados com o resíduo orgânico.…”
Section: Variávelunclassified
“…Benites and Mendonça (1998) observed that the addition of more than 15 Mg ha À1 of non-humified organic matter (manure) to soil changed the superficial electric potential and increased the dispersible clay content. In addition, Tavares Filho et al (2010) observed that doses of up to 48 Mg ha À1 sewage sludge increased the DpH (pH H 2 O -pH KCl ), indicating a change in the superficial electric potential, while not demonstrating an increase in clay dispersion compared to no application of sewage sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Soil aggregates are used as indicators of soil quality (Vrdoljak and Sposito, 2002) and can therefore be used to evaluate the effects of manure and sewage sludge disposal on soil quality (Hati et al, 2006;Lee et al, 2009;Bandyopadhyay et al, 2010;Tavares Filho et al, 2010;Villemin, 2011 Watteau et al, 2012). Over time, soil fertilisation with manure or sewage sludge can improve the physical properties of soil (Hati et al, 2006;Bandyopadhyay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Soil flocculation is associated with aggregation, because soil reaction to its content of charges is associated with dispersion, and these are physicochemical factors. Soil dispersion is also dependent on its mineralogy and electrochemical potential (ALBUQUERQUE et al, 2002;BARBOSA;RIBON, 2010). To understand this type of alteration, parameters such as ΔpH (pH KCl -pH H 2 O) and the point of zero charge (PZC) are used in these studies, which show the importance of these interactions of charges in soil flocculation, and consequently in its structure.…”
Section: Introductionmentioning
confidence: 99%